High, As Well As Low, Preoperative Platelet Counts Correlate With Adverse Outcomes After Elective Posterior Lumbar Surgery. Issue 5 (1st March 2020) - Malpani, Rohil; Gala, Raj J.; Adrados, Murillo; Galivanche, Anoop R.; Clark, Michael G.; Mercier, Michael R.; Pathak, Neil; Mets, Elbert J.; Grauer, Jonathan N.
Abstract : Study Design: Retrospective cohort study of prospectively collected data. Objective: Assess correlation between preoperative platelet counts and postoperative adverse events after elective posterior lumbar surgery procedures. Summary of Background Data: Preoperative low platelet counts have been correlated with adverse outcomes after posterior lumbar surgery. Nonetheless, the effect of varying platelet counts has not been studied in detail for a large patient population, especially on the high end of the platelet spectrum. Methods: Patients who underwent elective posterior lumbar surgery were identified in the 2011 to 2016 National Surgical Quality Improvement Program database. Preoperative platelet counts were considered relative to 30-day perioperative adverse outcomes. Patients were classified into platelet categories based on determining upper and lower bounds on when the adverse outcomes crossed a relative risk of 1.5. Univariate and multivariate analyses compared 30-day postoperative complications, readmissions, operative time, and hospital length of stay between those with low, normal, and high platelet counts. Results: In total, 137, 709 posterior lumbar surgery patients were identified. Using the relative risk threshold of 1.5 for the occurrence of any adverse event, patients were divided into abnormally low (⩽140, 000/mL) and abnormally high (≥447, 000/mL) platelet cohorts. The abnormally low and high platelet groups were associated with higher rates of any, major, minor adverse events, transfusion, and longer hospital length of stay. Furthermore, the abnormally low platelet counts were associated with a higher risk of readmissions. Conclusion: The data-based cut-offs for abnormally high and low platelet counts closely mirrored those found in literature. Based on these definitions, abnormally high and low preoperative platelet counts were associated with adverse outcomes after elective posterior lumbar surgery. These findings facilitate risk stratification and suggest targeted consideration for patients with high, as well as low, preoperative platelet counts. Level of Evidence: 3 Abstract : The current study assessed 137, 709 patients undergoing elective posterior lumbar surgery. On multivariate analysis, preoperative low (<140, 000/mL), as well as high (>447, 000/mL) platelet counts, correlated with adverse perioperative outcomes. These findings facilitate risk stratification and suggest targeted consideration for patients with high, as well as low, preoperative platelet counts.